Data for "Lithium-Sulfur Battery State-of-Charge Observability Analysis and Estimation" - Fotouhi, Abbas; Auger, Daniel; Propp, Karsten; Longo, Stefano (Cranfield University, 2017)
3.4 Ah Li-S cell pulse discharge test data at 30 degree. File created in MATLAB 2015a.
Keywords: lithium-sulfur'; 'battery'; 'pulse test data'; 'Automotive Mechatronics'